The Multidisciplinary Guidelines for Diagnosis and Referral in Cerebral Visual Impairment - Boonstra, Frouke N.; Bosch, Daniëlle G. M.; Geldof, Christiaan J. A.; Stellingwerf, Catharina; Porro, Giorgio (Frontiers in Human Neuroscience, 2022)
Introduction Cerebral Visual Impairment (CVI) is an important cause of visual impairment in western countries. Perinatal hypoxic-ischemic damage is the most frequent cause of cerebral visual impairment but CVI can also be the result of a genetic disorder. The majority of children with CVI have cerebral palsy and/ or developmental delay. Early diagnosis is crucial; however, there is a need for consensus on evidence based diagnostic tools and referral criteria. The aim of this study is to develop guidelines for diagnosis and referral in CVI according to the grade method. Patients and methods We developed the guidelines according to the GRADE method 5 searches on CVI (children, developmental age ≤18 years) were performed in the databases Medline, Embase and Psychinfo, each with a distinct topic. Results Based on evidence articles were selected on five topics: 1 Medical history and CVI-questionnaires 23 (out of 1007) 2 Ophthalmological and orthoptic assessment 37 (out of 816) 3 Neuropsychological assessment 5 (out of 716) 4 Neuroradiological evaluation and MRI 9 (out of 723) 5 Genetic assessment 5 (out of 458) Conclusions In medical history taking, prematurity low birth weight and APGAR (Appearance, Pulse, Grimace, Activity, Respiration) Scores (<5) are important. Different questionnaires are advised for children under the age of 3 years, older children and for specific risk groups (extremely preterm). In ophthalmological examination, eye movements, specially saccades, accommodation, crowding, contrast sensitivity and visual fields should be evaluated. OCT can show objective signs of transsynaptic degeneration and abnormalities in fixation and saccades can be measured with eye tracking. Screening of visual perceptive functioning is recommended and can be directive for further assessment. MRI findings in CVI in Cerebral Palsy can be structured in five groups (brain maldevelopment, white and grey matter lesions, postnatal lesions and a normal MRI). In children with CVI and PVL (periventricular leukomalacia), brain lesion severity correlates with visual function impairment. A differentiation can be made between cortical and subcortical damage and related visual function impairment. Additional assessments (neurological or genetic) can be necessary to complete the diagnosis of CVI and/or to reveal the etiology.